Implementing Carbon Tariffs : A Fool’s Errand? - Moore, Michael O. (2012)
Some governments are considering taxes on imports based on carbon content from countries that have not introduced climate change policies. Such carbon border taxes appeal to domestic industries facing higher charges for their own carbon emissions. This research demonstrates that there are enormous practical difficulties surrounding such plans. Various policies are evaluated according to World Trade Organization compliance, administrative plausibility, help in meeting environmental goals, and ability to deal with domestic pressures. The steel industry is used as a case study in this analysis. All considered policies arguably fail to meet at least one of these constraints, bringing into question the plausibility that a carbon border tax can be practical policy.